1967
DOI: 10.1172/jci105695
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Lipid Depletion in Hyperpermeable Red Blood Cells: Its Role in the Genesis of Spherocytes in Hereditary Spherocytosis*

Abstract: Abstract. Hereditary spherocytosis (HS) red cells lose membrane lipids excessively during incubation in vitro. Individual phosphatides as well as cholesterol are lost in proportion to their content in membranes, suggesting that fragments of membrane are removed. Supplementation of HS red cells with glucose during incubation has no consistent protective effect, whereas diminishing the excessive sodium flux through these cells by suspending them in either sodium-free or hypertonic media prevents membrane fragmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

1968
1968
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 30 publications
0
24
0
1
Order By: Relevance
“…In contrast to this selective loss of red cell cholesterol, two recent studies have shown that red cells incubated in vitro lose both cholesterol and phospholipid, that they are lost in equivalent amounts, and that more is lost from hereditary spherocytosis (HS) than from normal red cells (9,10,17). HS cells are of particular interest because of their inordinate susceptibility to splenic pool- 906 The Journal of Clinical Investigation Volume 48 1969 ing exposing them to the conditions of erythrostasis (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this selective loss of red cell cholesterol, two recent studies have shown that red cells incubated in vitro lose both cholesterol and phospholipid, that they are lost in equivalent amounts, and that more is lost from hereditary spherocytosis (HS) than from normal red cells (9,10,17). HS cells are of particular interest because of their inordinate susceptibility to splenic pool- 906 The Journal of Clinical Investigation Volume 48 1969 ing exposing them to the conditions of erythrostasis (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Jacob (13) has also suggested that the greater phospholipid turnover in HS RBC, as measured by 82p incorporation, is causally related to the loss of lipid and membrane fragmentation which these cells undergo. Previous work from this laboratory (11,12) has suggested that premature alteration in the physical properties of the membrane protein in HS RBC resulting from ATP depletion was the critical factor in producing loss of membrane substance in these cells.…”
Section: Resultsmentioning
confidence: 99%
“…They 'report that the labeling of PS is increased by a factor of about two in the erythrocytes of patients with hereditary spherocytosis (HS RBC). They suggest that this increase is due to the greater rate of Na+ transport in these cells, and that this increased phospholipid turnover is responsible for the loss of lipid and membrane fragmentation found in HS RBC (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…However, spherical red cells. 4 Decrease in OF (more resistant to hemolysis) OFT may not be an effective screening technique in the areas has been observed in thalassemia, iron deficiency, some forms of where iron deficiency is prevalent, such as in Egypt. 14 In spite of liver diseases and lead poisoning.…”
Section: Introductionmentioning
confidence: 99%